Veblen's institutionalist elaboration of rent theory - Michael Hudson (Levy Economics Institute of Bard College, 2012)
As the heirs to classical political economy and the German historical school, the American institutionalists retained rent theory and its corollary idea of unearned income. More than any other institutionalist, Thorstein Veblen emphasized the dynamics of banks financing real estate speculation and Wall Street maneuvering to organize monopolies and trusts. Yet despite the popularity of his writings with the reading public, his contribution has remained isolated from the academic mainstream, and he did not leave behind a school. Veblen criticized academic economists for having fallen subject to trained incapacity as a result of being turned into factotums to defend rentier interests. Business schools were painting an unrealistic happy-face picture of the economy, teaching financial techniques but leaving out of account the need to reform the economy's practices and institutions. In emphasizing how financial predation was hijacking the economy's technological potential, Veblen's vision was as materialist and culturally broad as that of the Marxists, and as dismissive of the status quo. Technological innovation was reducing costs but breeding monopolies as the finance, insurance, and real estate (FIRE) sectors joined forces to create a financial symbiosis cemented by political-insider dealings - and a trivialization of economic theory as it seeks to avoid dealing with society's failure to achieve its technological potential. The fruits of rising productivity were used to finance robber barons who had no better use of their wealth than to reduce great artworks to the status of ownership trophies and achieve leisure-class status by funding business schools and colleges to promote a self-congratulatory but deceptive portrayal of their wealth-grabbing behavior.
Keywords: B15; G02; 330; History of Economic Thought; Institutionalism; FIRE Sector; Financialization